Long-Term In Vitro System for Maintenance and Amplification of Root-Knot Nematodes in Cucumis sativus Roots - Díaz-Manzano, Fernando E.; Olmo, Rocío; Cabrera, Javier; Barcala, Marta; Escobar, Carolina; Fenoll, Carmen (Frontiers in Plant Science, 2016)
Root-knot nematodes (RKN) are polyphagous plant-parasitic roundworms that produce large crop losses, representing a relevant agricultural pest worldwide. After infection, they induce swollen root structures called galls containing giant cells (GCs) indispensable for nematode development. Among efficient control methods are biotechnology-based strategies that require a deep knowledge of underlying molecular processes during the plant-nematode interaction. Methods of achieving this knowledge include the application of molecular biology techniques such as transcriptomics (as massive sequencing or microarray hybridization), proteomics or metabolomics. These require aseptic experimental conditions, as undetected contamination with other microorganisms could compromise the interpretation of the results. Herein, we present a simple, efficient and long-term method for nematode amplification on cucumber roots grown in vitro. Amplification of juveniles (J2) from the starting inoculum is around 40-fold. The method was validated for three Meloidogyne species (Meloidogyne javanica, M. incognita, and M. arenaria), producing viable and robust freshly hatched J2s. These J2s can be used for further in vitro infection of different plant species such as Arabidopsis, tobacco and tomato, as well as to maintain and amplify the population. The method allowed maintenance of around 90 Meloidogyne sp. generations (one every 2 months) from a single initial female over 15 years.